Rancang Bangun Aplikasi Point Of Sales Berbasis Web Dengan Arsitektur MVC Menggunakan Framework Laravel Di PT Palokoto Agro Industri - As'ari, Azi; Hadiwandra, T. Yudi (Computer Science and Information Technology, 2025)
PT Palokoto Agro Industri still relies on Microsoft Excel for warehouse record-keeping, which is ineffective for managing large-scale data, prone to errors, and lacks security. The manual stock update process increases workload and reduces data accuracy. Furthermore, the absence of real-time access limits managers in monitoring warehouse activities and making timely decisions. To address these issues, this study developed a web-based Point Of Sales (POS) application. The application was built using the Model-View-Controller (MVC) architecture and the Laravel framework, equipped with features that align with warehouse recording standards, such as managerial access, automatic calculation of incoming and outgoing goods, and fast report generation. This research applied the Research and Development (R&D) method with a prototyping approach. The application was evaluated using the ISO/IEC 25010 standard, and the results showed that it fulfilled all aspects of software quality, including functional suitability, reliability, usability, performance efficiency, maintainability, portability, compatibility, and security. Therefore, the developed application meets the required quality criteria and can serve as a structured solution for warehouse record-keeping at PT Palokoto Agro Industri.